Pengembangan Sistem Manajemen Perusahaan Sablon Kaos Berbasis Website Menggunakan Metode Prototyping (Studi Kasus: Perusahaan Sablon di Kota Malang) - Muhammad Rayyan Abhad; Achmad Arwan; Djoko Pramono (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
T-shirt screen printing is a printing technique above t-shirt using a tool called a ‘screen' or commonly called a ‘screen printing film'. T-shirt screen printing services nowadays have developed to become a promising business because of more needs from society. Nalar Industries, Trilogy Screen printing, and Mixone are a few examples of t-shirt screen printing companies in Malang which can produce about 100 to 150 t-shirts per day. In their development, these companies find the problems in several things such as order process, production management, and financial records. Therefore, a website-based company management system was created to managing the order process, managing the production, and recording the financial with more effective and efficient. The development of this system uses the prototyping method because user's requrements haven't been clearly identified. Requirement analysis of this research produces 4 actors, 30 functional requirements, and 1 non-functional requirement. The software testing uses some strategies, such as unit testing, integration testing, and validation testing. Based on the result of the software testing obtained prove that the system runs as expected. Besides that, there is compatibility testing that prove the system runs as well in various browsers and devices.